2013
DOI: 10.1158/1538-7445.am2013-2042
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2042: TOB1 promotes cell survival in estrogen-independent estrogen receptor-positive breast cancer.

Abstract: Antiestrogens are the most widely administered endocrine agents for the treatment of estrogen receptor (ER)-expressing breast cancers, such as tamoxifen, fulvestrant and aromatase inhibitor. However, most initially responsive breast tumors acquire resistance and become estrogen-independent. To find potential therapeutic target(s) against drug resistance, we performed siRNA library screening studies to identify cell survival determinants in estrogen independent cell lines from 631 ER network related genes. LCC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The EtOAc-soluble portion of the EtOH extract was repeatedly subjected to silica gel and Sephadex LH-20 column chromatography, followed by reversed-phase semipreparative HPLC purification, providing four new prenylated bibenzyls (2, 4-6) and two known analogues (7,8). By comparing their observed and reported spectroscopic data, the known bibenzyls were identified as 3,5-dihydroxy-2-[3,7-dimethyl-2(E), 6octadienyl] bibenzyl (7) 16) and 3,5-dihydroxy-2-(3-methyl-2-butenyl) bibenzyl (8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The EtOAc-soluble portion of the EtOH extract was repeatedly subjected to silica gel and Sephadex LH-20 column chromatography, followed by reversed-phase semipreparative HPLC purification, providing four new prenylated bibenzyls (2, 4-6) and two known analogues (7,8). By comparing their observed and reported spectroscopic data, the known bibenzyls were identified as 3,5-dihydroxy-2-[3,7-dimethyl-2(E), 6octadienyl] bibenzyl (7) 16) and 3,5-dihydroxy-2-(3-methyl-2-butenyl) bibenzyl (8).…”
Section: Resultsmentioning
confidence: 99%
“…500-1600 m altitude, is widely distributed throughout southwestern China. 4) Members of the genus Aglaia have been studied extensively, resulting in the isolation of many types of interesting secondary metabolites, particularly of various triterpenoids (e.g., cycloartanes, dammaranes, tirucallanes) and flavaglines (e.g., cyclopenta [b] [8][9][10] In an ongoing research for biologically active substances from various natural sources, 11-15) the plant A. abbreviata attracted our attention because the ethyl acetate (EtOAc) extract of the leaves of this plant showed inhibitory activity against PTP1B with an 65.2% inhibition at the concentration of 20 µg/mL. As a result, four new (aglaiabbrevins A-D, 2, 4-6) and two known (7, 8) prenylated bibenzyls were isolated (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The plant is used in Indonesian folk medicine for the treatment of fever, diarrhea, contused wound, coughs and skin diseases. 4 Previous phytochemical studies on Aglaia plants reported the presence of rocaglamide, 5,6,7 bisamides, 8,9 sesquiterpenoids, 10,11 diterpenoids, 12,13 dammaranetype triterpenoids, [14][15][16] cycloartane-type triterpenoids, 17,18 and apotirucallane triterpenoids. 19,20 Although secondary metabolites of other Aglaia species have been investigated previously, the chemical composition of A. ellipticais yet to be reported.…”
Section: Introductionmentioning
confidence: 99%